Statistical process control applied in the analysis of defects in asynchronous electrical machines - Nutu, Catalin Silviu (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper refers to defects recorded for asynchronous electrical motors. The aim of this paper is to conclude about the quality of the production process of the asynchronous electrical machines using the statistical process control. The main objective of statistical process control is to find and conclude about the abnormalities in the production processes, using statistical tools of analysis and control, the so called quality control charts. For a certain measured quality characteristic, analyzing the corresponding control chart of that characteristic, one can conclude about the fact whether the respective process is getting out of the control or it is under control. These conclusions are made using the so called control limits, LCL and UCL (lower and upper control limit).